The Crisis in Fiqh and the Methodology of ljtihad - Taha J. al 'Alwani (International Institute of Islamic Thought, 1991)
The year 310 AH (922 AC), the year in which the last of the acknowledged mujtahidun died, may be marked as the beginning of the crisis of fiqh that continues even to this day. At that time Islamic fiqh took a very serious turn and, near the end of the fourth hijri century, its most negative effects began to be apparent. It was then that the thmkmg of scholars was seriously influenced by the apprehension that certain rulers, through their citing permission obtained as the result of the misuse of fiqh, were exploiting the things held dear by the ummah. Thus it was out of fear that the idea of closing the door of ijtihad was born. This essentially defensive notion was accomplished by stipulations to the effect that recourse might only be had to the ijtihad made by the scholars of the earliest generations, that no changes could be made to the ijtihad performed by them, and that any opinion that did not conform to their opinions should be rejected. In this way, the sun set on true ijtihad, and in its place there came mere taqlid, which allowed the state of legal and intellectual lassitude to become widespread. Moreover, the ties of the ummah to the two sources of legislation, the Qur'an and the Sunnah, and to the other sources weakened and then fell away entirely. Finally, fiqhi studies were confined to a few specific textbooks, commentaries on those textbooks, commentaries on the commentaries, and annotations on the commentaries on the commentaries. Let us see how al Ghazzali (505 AH/1111 AC) described the situation, and how his explanation included mention ofthe most important developments to take place in Shari‘ah studies in general and in fiqh in particular. He wrote: You must know that the office of khliafah after the Prophet of Allah, upon him be peace, was assumed by the al khulafa’ al rashidun, who were imams and Shari’ah scholars in their awn right. Moreover, they were active in giving futiiwii and making legal judgments. Therefore, only rarely if ever did they need to seek the opinions of the fuqaha’. The result of this was that the fuqaha’ immersed themselves in knowledge of the next world and shunned all else. Thus, they were known for their refusals to give fatawa and legal advice on issues of worldly import, perferring instead to devote all of their deductive abilities to the worship of Allah Most High. But when, soon after the deaths of the al khulafa' al rashidun, the office of khalifah passed into the hands of those unqualified to lead the ummah and unlearned in matters of fiqh and fatwa, it became necessary to consult the fuqaha’ and to seek their advice in nearly everything. At that time, there still remained of the successor generation (the Tabi’un) those who continued in the same way as before, practicing Islam in complete purity, and following the example of the most learned and devout from their predecessors. Thus, if they were sought out (by those in power who would ask them questions), they would flee or otherwise evade them. The result of this attitude was that the rulers had to resort to pressuring scholars to accept positions as qadis and government ...